Procedure for Handling 4-H Accounts: Guidelines for Creating Accounts - Marilyn N. Norman; Joy C. Jordan (EDIS)
4H5.2, a 3-page factsheet by Marilyn N. Norman and Joy C. Jordan, explains how to properly establish, create and manage 4-H bank accounts. Includes information about obtaining an IRS Employer Identification Number. Published by the UF Department of Family, Youth and Community Sciences, February 2007.